Social policy review. edited by Gaby Ramia, Kevin Farnsworth, Zoë Irving. - Ramia, Gaby; Farnsworth, Kevin; Irving, Zoë (The Policy Press, 2013)
This latest edition of Social Policy Review presents an up-to-date and diverse review of the best in social policy scholarship with a special focus on work, employment and insecurity.